Pengambangan Kurikulum PAUD Berbasis Hadis: Syistematic Literature Review - audiah, izhanoem; Marhumah; Iffah Khoiriyatul Muyassaroh (STAI Nurul Qadim, 2025)
The development of an Early Childhood Education (ECE) curriculum based on hadith is a response to the need for a framework that systematically instills moral and spiritual values from an early age. As an authentic source of Islamic teachings, hadith is considered to have great potential in shaping the character of virtuous children through a holistic and contextual educational approach. This study aims to formulate a conceptual foundation for the development of a hadith-based ECE curriculum that is not only theoretically relevant but also practically applicable. Using a Systematic Literature Review (SLR) approach, this research identifies and analyzes 30 scholarly articles published between 2020 and 2025 related to early childhood education based on Islamic values in the Southeast Asian context. The results indicate that integrating hadith values such as honesty, compassion, responsibility, and politeness can be effectively implemented through play-based activities, daily routines, and child-friendly digital learning media. Additionally, the roles of teachers, the validity of hadith, and curriculum management are critical factors in the successful implementation of this curriculum. The study concludes that a hadith-based ECE curriculum is both urgent and highly potential in shaping a Qur’anic generation that is spiritually grounded, morally resilient, and adaptable to the demands of the times. Therefore, synergy among educators, educational institutions, and the broader community is essential in realizing an Islamic, practical, and joyful learning environment.